Targetable Immune Regulatory Molecule Expression in High-Grade Serous Ovarian Carcinomas in African American Women: A Study of PD-L1 and IDO in 112 Cases From the African American Cancer Epidemiology Study (AACES). (March 2019) - Mills, Anne M.; Peres, Lauren C.; Meiss, Alice; Ring, Kari L.; Modesitt, Susan C.; Abbott, Sarah E.; Alberg, Anthony J.; Bandera, Elisa V.; Barnholtz-Sloan, Jill; Bondy, Melissa L.; Cote, Michele L.; Funkhouser, Ellen; et al.
Abstract : African American women with high-grade serous ovarian carcinoma have worse outcomes compared with women of European descent. Although the discrepancy is partially attributed to differences in access to care, the tumor immune microenvironment may also contribute. Expression of targetable immune regulatory molecules such as programmed cell death ligand-1 (PD-L1) and indoleamine 2, 3 dioxygenase (IDO) is of particular interest as it may help guide therapy in this population. Using cases from the largest study of African American women with ovarian cancer, the African American Cancer Epidemiology Study, we characterized PD-L1 and IDO expression in 112 high-grade serous ovarian carcinomas. Immunohistochemistry for PD-L1, IDO, CD8, FOX3p, and CD68 was performed. PD-L1 and IDO were scored as the percentage of positive tumor cells and tumor-associated immune cells. CD8 and FOX3p counts were averaged across 10 high-power fields. Cox proportional hazards regression was used to evaluate the association between PD-L1 and IDO expression and survival. Tumor cells were positive for PD-L1 and IDO in 29% and 58% of cases, respectively. The majority showed <10% staining, and no cases exceeded 25% positivity. The majority of PD-L1-positive cases coexpressed IDO. PD-L1 and IDO expression was associated with higher CD8 and FOX3p counts ( P <0.05). No association was observed between PD-L1 and IDO and survival. In summary, expression of PD-L1 and IDO is seen in a subset of high-grade serous ovarian carcinoma from African American women and is correlated with elevated lymphocyte infiltration. While PD-L1 and IDO co-expression suggests a role for dual immunotherapy, diffuse expression of PD-L1 and IDO is rare, invoking caution regarding the potential for immunotherapeutic response. Abstract : Supplemental Digital Content is available in the text.